COMPARATIVE ANALYSIS OF MIRSIDDIQHAN HASHMAT BUKHORI TAZKIRAS WITH OTHER TAZIRS - Temirov , Sheroz Turayevich (Innovative Development in Educational Activities, 2022)
Mirsiddikhan Hashmati Bukharoy is one of the famous poets and poets of Tajik literature and is famous for his literary and historical works. There are reports that Mirsiddiq Khan Hashmat knew Persian, Arabic and Turkish well and wrote his tazkira and works in these languages.